Bleeding in patients with atrial fibrillation treated with combined antiplatelet and anticoagulant therapy: time to turn the corner - Xu, Ke; Chan, Noel C. (Annals of Translational Medicine, 2019)
Anticoagulation is the mainstay for stroke prevention in patients with atrial fibrillation (AF). Many patients with AF also have a concomitant indication for either single or dual antiplatelet (aspirin plus a P2Y12 inhibitor) therapy. For instance, about 1 in 3 patients with AF have coexistent coronary artery disease, and about 1 in 5 undergo percutaneous coronary intervention (PCI) (1). Although anticoagulant therapy is more effective than either single or dual antiplatelet therapy (DAPT) for stroke prevention in AF, guidelines recommend DAPT over vitamin K antagonist (VKA) for the prevention of coronary stent thrombosis. Such quandary prompted the addition of DAPT to an anticoagulant, also known as triple therapy, with the intent of preventing both coronary ischemic and cardioembolic events (2).